Pengaruh Profitabilitas dan Likuiditas Terhadap Financial Distress dengan Struktur Modal sebagai Pemoderasi - Afsari Nuhun, Ilham Muhammad; Eky Pambudi, Januar (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This research intends to investigate the relationship between profitability and liquidity on financial distress, with capital structure serving as a moderating factor in firms listed on the Indonesia Stock Exchange within the basic and chemical sectors. The sample comprised 18 companies from the food and beverage industry, chosen according to the criteria of annual reports released between 2019 and 2023. The method utilized for sampling is purposive sampling. The analysis of the data was conducted through panel data moderation regression utilizing Eviews12. The findings of this research show that profitability and liquidity positively influence financial distress. The capital structure cannot serve as a moderating variable affecting the relationship between profitability and financial distress. In contrast, the capital structure can diminish the impact of liquidity on financial hardship.